Runaway electron studies with hard x-ray and microwave diagnostics in the FT-2 lower hybrid current drive discharges. (23rd November 2017) - Shevelev, A.E.; Khilkevitch, E.M.; Lashkul, S.I.; Rozhdestvensky, V.V.; Pandya, S.P.; Plyusnin, V.V.; Altukhov, A.B.; Kouprienko, D.V.; Chugunov, I.N.; Doinikov, D.N.; Esipov, L.A.; Gin, D.B.; et al.
Abstract: Studies of the super-thermal and runaway electron behavior in ohmic and lower hybrid current drive FT-2 tokamak plasmas have been carried out using information obtained from measurements of hard x-ray spectra and non-thermal microwave radiation intensity at the frequency of 10 GHz and in the range of (53 ÷ 78) GHz. A gamma-ray spectrometer based on a scintillation detector with a LaBr3 (Ce) crystal was used, which provides measurements at counting rates up to 10 7 s −1 . Reconstruction of the energy distribution of RE interacting with the poloidal limiter of the tokamak chamber was made with application of the DeGaSum code. Super-thermal electrons accelerated up to 2 MeV by the LH waves at the high-frequency pumping of the plasma with low density ⟨ n e ⟩ ~ 2  ×  10 13 cm −3 and then up to 7 MeV by vortex electric field have been found. Experimental analysis of the runaway electron beam generation and evolution of their energy distribution in the FT-2 plasmas is presented in the article and compared with the numerical calculation of the maximum energy gained by runaway electrons for given plasma parameters. In addition, possible mechanisms for limiting the maximum energy gained by the runaway electrons are also calculated and described for a FT-2 plasma discharge.